"Quantum Weirdness" in Exploitation by the International Gravitational‐Wave Observatory Network. Issue 3 (29th January 2020) - Schnabel, Roman
Abstract: The detectors of the international gravitational‐wave (GW) observatory network are currently taking data with sensitivities improved via squeezing the photon counting noise of the laser light used. Several GW candidate events, such as black‐hole mergers, are already in the pipeline to be analyzed in detail. While the brand‐new field of GW astronomy relies on squeezed light for reaching higher sensitivities, the physical understanding of such light, although being well described by quantum theory, is still under discussion. Herein, a physical description of why squeezed light, as now being exploited by GW observatories, constitutes rather remarkable physics is presented. Consideration of the Fourier transform seems to provide an argument why the measurement of squeezed photon statistics from quasi‐monochromatic light is "weird." It is further argued that the measurement of squeezed photon statistics is related to the famous gedanken experiment formulated by Einstein, Podolsky, and Rosen in 1935. This work illuminates "quantum weirdness" in a clear way and might be the starting point for finding the physics of quantum correlations in general, which scientists have been seeking for decades. Abstract : Since April 2019, all gravitational‐wave observatories worldwide have been using quantum‐squeezed laser light for their observations. The observed event rate has increased by up to 50%. Although being well described by quantum theory, the physical understanding of squeezed light, however, is still under discussion. "Quantum weirdness" is found by considering the Fourier transform of the rather monochromatic laser light used.